2017
DOI: 10.1177/2045893217723594
|View full text |Cite
|
Sign up to set email alerts
|

Portopulmonary hypertension in children: a rare but potentially lethal and under‐recognized disease

Abstract: Portopulmonary hypertension (PoPH) is defined by the combination of portal hypertension and precapillary pulmonary arterial hypertension (PAH). Very little is known about this process in pediatric patients but prognosis is generally poor. We review our institutional experience and report on five patients with pediatric PoPH. The median age of PoPH diagnosis was six years and PAH was 14 years. PAH diagnosis was made by echocardiogram in all patients, four of whom also had cardiac catheterization. The median mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…We speculate that the dominance of CHD-PAH over IPAH in our population might be attributable to the longer survival of patients with PAH, due to cardiac defects, than IPAH patients [24], however, the exact cause of the CHD-PAH dominance is not known. In the present study, we found only one patient with PoPAH (a condition rarely diagnosed in children [25]), and no patient was diagnosed with other forms of associated PAH, including CTD-PAH. Although these types of PAH were also very rare in other registry studies 10 (4.6%) patients with CTD-PAH and three (1.4%) patients with PoPAH in the REVEAL registry [4], our data suggest the need for building an awareness of PAH in pediatricians specializing in children rheumatology and hepatology.…”
Section: Pah Classificationcontrasting
confidence: 50%
“…We speculate that the dominance of CHD-PAH over IPAH in our population might be attributable to the longer survival of patients with PAH, due to cardiac defects, than IPAH patients [24], however, the exact cause of the CHD-PAH dominance is not known. In the present study, we found only one patient with PoPAH (a condition rarely diagnosed in children [25]), and no patient was diagnosed with other forms of associated PAH, including CTD-PAH. Although these types of PAH were also very rare in other registry studies 10 (4.6%) patients with CTD-PAH and three (1.4%) patients with PoPAH in the REVEAL registry [4], our data suggest the need for building an awareness of PAH in pediatricians specializing in children rheumatology and hepatology.…”
Section: Pah Classificationcontrasting
confidence: 50%
“…Whereas HPS is characterised by increased pulmonary blood flow, low PVR and hypoxaemia, POPH has striking pulmonary vascular remodelling that adversely affects the outcome of orthotopic liver transplantation [23]. POPH appears to be rare in children, with 0–2% of cases reported in PH registries [5, 6, 22, 24].…”
Section: Updates In Paediatric Ph Epidemiology and Classificationmentioning
confidence: 99%
“…Small paediatric studies suggest a very poor outcome in children. 5 Our aim was to report on our realworld experience of PoPH management in a specialised centre, with the aim of increasing awareness and improving management of these patients.…”
Section: Introductionmentioning
confidence: 99%